2008
DOI: 10.1086/589884
|View full text |Cite
|
Sign up to set email alerts
|

α+‐Thalassemia Protects against Anemia Associated with Asymptomatic Malaria: Evidence from Community‐Based Surveys in Tanzania and Kenya

Abstract: alpha(+)-Thalassemia limits the decline in hemoglobin concentration that is associated with afebrile infections, particularly those that are accompanied by inflammation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
41
2
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(49 citation statements)
references
References 37 publications
4
41
2
1
Order By: Relevance
“…This compares to other works that have suggested that alpha+ thalassaemia might limit the decline in haemoglobin that is not only confined to severe malaria cases but even so the protective effect might be evident when the Plasmodium falciparum infection is accompanied by inflammation (Veenemans et al, 2008).…”
contrasting
confidence: 74%
See 4 more Smart Citations
“…This compares to other works that have suggested that alpha+ thalassaemia might limit the decline in haemoglobin that is not only confined to severe malaria cases but even so the protective effect might be evident when the Plasmodium falciparum infection is accompanied by inflammation (Veenemans et al, 2008).…”
contrasting
confidence: 74%
“…Malaria generally causes haemolysis and therefore a reduction in the haemoglobin concentration. However, among alpha + -thalassaemic patients is a gradual decline in the haemoglobin concentration (Veenemans et al, 2008) thus conferring protection against SMA in children.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations